Comparative study between nutrient-enriched zeolites and conventional fertilizers: effect on kale growth - Aparecida Santos, Nathalia; Chieko Shinzato, Mirian; de Toledo Castanho, Camila (Revista Ceres, 2024)
Synthetic fertilizers have high solubility and when leached through the soil can have environmental and economic impact. Minerals with high cationic exchange capacity, such as zeolites, can reduce nutrient loss. We compared the effect of zeolites enriched with nutrients (NH4+ and K+) and conventional fertilizers on kale growth. Experiments were conducted with 30 pots containing a substrate with: (i) nutrient-enriched zeolites and a phosphate salt (Z-NK+P); (ii) NH4+, K+ and P salts (NPK); (iii) no additional nutrients (control). After three months, we evaluated kale productivity, absorption of nutrients and nutrient loss on the percolated water. The Z-NK+P and NPK treatments had a higher kale growth and retained more water volume in the first and third month, compared to the control. The NPK treatment released more NH4 + (54%) and K+ (92.9%) in percolated water than the zeolite treatment (15.5% K+ and 22.4% NH4+) in all the comparisons and had a higher K+ concentration in its leaves than control. Both fertilizations were efficient in providing nutrients to the plants; however, zeolites present the advantage by releasing the nutrients gradually, reducing their loss and potentially minimizing environmental and economic impact.